Teachers' Intervention Strategies for Reading Difficulties Among Second-Grade Students: A Qualitative Case Study in Primary Education - Nur Rahmi Rezki Ramadhani; Rizal Rizal; Muhammad Aqil; Surahman Wilade (Papanda Publisher, 2026)
Reading difficulties among early-grade students constitute a critical concern in Indonesian primary education, yet empirical documentation of teachers' intervention practices in authentic classroom settings remains limited. This qualitative case study examined teachers' efforts in addressing reading difficulties among four second-grade students at SD Negeri Beka, employing observations, semi-structured interviews, and documentation analysis over two academic semesters. Data were analyzed using Miles and Huberman's framework, with triangulation ensuring trustworthiness. Three primary factors contributed to reading difficulties: phonological awareness deficits (letter recognition and decoding challenges), limited parental support and home literacy environments, and motivational challenges. Teachers implemented multiple interventions including picture word cards for multisensory instruction, daily supplementary reading sessions providing additional instructional time, and provision of developmentally appropriate materials with large print and illustrations. Longitudinal observations documented gradual improvements in students' decoding accuracy, reading fluency, and self-efficacy, though progress remained incomplete and varied across individual learners. While teachers demonstrated commitment and creativity, gaps existed between implemented practices and evidence-based intervention components, particularly regarding explicit systematic phonics instruction and progress monitoring. Findings underscore the need for professional development programs equipping Indonesian teachers with research-validated intervention strategies while building upon existing pedagogical strengths and contextual awareness.